Serum cytokines, interleukin-2 receptor, and soluble intercellular adhesion molecule-1 in oral disorders - Yamamoto, Tetsuya; Yoneda, Kazunori; Ueta, Eisaku; Osaki, Tokio (Oral surgery, oral medicine, oral pathology, 1994)
Serum levels of soluble intercellular adhesion molecule-1, soluble interleukin-2 receptor, and cytokines such as interleukin-3, interleukin-4, interleukin-6, tumor necrosis factor-α, and granulocyte-macrophage colony-stimulating factor were examined in patients with oral disorders with 20 healthy persons used as control subjects. Patients studied included 30 with squamous cell carcinoma, 26 with oral lichen planus, 20 with recurrent aphthous ulcer, 19 with acute odontogenic bacterial infection, 16 with pseudomembranous candidiasis, and 16 with herpetic gingivostomatitis. Compared with levels in control subjects, detectable serum levels of interleukin-3 (≧ 10 pg/ml) existed more frequently in pseudomembranous candidiasis ( 13 16 ), acute odontogenic bacterial infection ( 14 19 ), and squamous cell carcinoma ( 24 30 ) and of granulocyte-macrophage colony-stimulating factor (≧ 4 pg/ml) more frequently in recurrent aphthous ulcer ( 15 20 ) and squamous cell carcinoma ( 21 30 ). These cytokine levels were increased with T stage of squamous cell carcinoma. About 20 pg/ml of interleukin-4 was detected in serum from one third to one fourth of patients with oral lichen planus, recurrent aphthous ulcer, and squamous cell carcinoma. Tumor necrosis factor-α was hardly detected in most patients except those with oral lichen planus and squamous cell carcinoma in which about one third of the patients had more than 40 pg/ml of tumor necrosis factor-α in serum. More than 10 pg/ml of interleukin-6 was frequently detected in all disorders, especially recurrent aphthous ulcer ( 18 20 ), pseudomembranous candidiasis ( 12 16 ), and acute odontogenic bacterial infection ( 17 19 ). After treatment, the serum interleukin-6 level increased in pseudomembranous candidiasis, acute odontogenic bacterial infection, herpetic gingivostomatitis, and squamous cell carcinoma, but decreased in oral lichen planus and recurrent aphthous ulcer. As compared with levels in the control subjects, significantly higher levels of soluble intercellular adhesion molecule-1 were observed in recurrent aphthous ulcer, herpetic gingivostomatitis, and pseudomembranous candidiasis and levels of soluble interleukin-2 receptor were significantly increased in oral lichen planus, recurrent aphthous ulcer, and pseudomembranous candidiasis. These results seem to indicate the immunologic characteristics of the individual oral disorder.